Finite Groups with Given Systems of Conditionally Seminormal Subgroups - Trofimuk, A. A. (Lobachevskii journal of mathematics, 2024)
The subgroups and are said to be cc-permutable, if permutes with for some . A subgroup of a finite group is called conditionally seminormal subgroup of , if there exists a subgroup of such that and is cc-permutable with all subgroups of . In this paper, we proved that saturated formation containing the class of all supersoluble groups is closed under product of conditionally seminormal -subgroups and with nilpotent derived subgroup or . In addition, we studied the structure of a group with given systems of conditionally seminormal subgroups.